Benin Influence on Isua Chieftaincy Titles: A Historical Exploration - Faboyede, Olusanya (European Scientific Journal, ESJ, 2022)
The influence of geography and migration on group relations in the periphery border areas of northeastern Yorubaland with the Edo-speaking people cannot be over-emphasised. Migration of people profoundly influenced cultural diffusion in towns and villages in Yorubaland, including Isua in Akokoland. In spite of cultural influence of the Benin kingdom on the people of border communities in the frontier zone of northeastern Yorubaland, the available earlier scholarly works mainly focused on how cultural evolution started in Ile-Ife, and the effects on towns and villages in the forest zone of Yorubaland without examining Benin’s influence on Isua chieftaincy titles in the pre-colonial period. This omission has created a vacuum in Yoruba historiography. This is the gap this study intends to fill. The study adopts the narrative approach and critical evaluation of data collected in order to discuss Benin influence on Isua chieftaincy titles in pre-colonial period.